О достаточных условиях разрешимости игровых задач сближения в классе стробоскопических стратегий - Чикрий, А.А.; Раппопорт, И.С. (Теорія оптимальних рішень, 2005)
In this paper the quasilinear differential games of pursuit are treated in the class of strobostrophic strategies. Sufficient conditions for solvability of pursuit problem are obtained. This research is based on the method of resolving functions.